Aerobic respiration Lactococcus lactis ameliorate Salmonella induced infection and intestinal dysfunctions by oxygen-scavenging and maintaining immune balance and regulating intestinal microbiota - Yulong Zhang; Han Yang; Zhiliang Cheng; Hui Ha; Fei Liu; Yuehua Jiao (Food Science and Human Wellness)
Salmonella grows better under aerobic conditions as a facultative anaerobic foodborne pathogenic bacteria. The oxygen-scavenging activity of Lactococcus lactis in the intestinal tract is a promising strategy for preventing Salmonella infection. In this study, the aerobic respiration requirement and preventive mechanism of L. lactis subsp. lactis KLDS 4.0325 in murine models infected by Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) SL1344 were investigated. Results indicate that L. lactis KLDS 4.0325 is capable of aerobic respiratory metabolism in the host intestine when exogenous heme exists, and decrease intestinal oxygen concentration, which in turn trigger autophagy of intestinal cells to reduce S. Typhimurium load, improve gut microbiota composition, alleviate intestinal barrier injury and inflammation response. These results suggest that aerobic respiration L. lactis KLDS 4.0325 can prevent S. Typhimurium infection in a new way in which by restoring intestinal cell hypoxia, maintaining immune balance and regulating intestinal flora.